2011
DOI: 10.1371/journal.pone.0016399
|View full text |Cite
|
Sign up to set email alerts
|

Standing Genetic Variation in Contingency Loci Drives the Rapid Adaptation of Campylobacter jejuni to a Novel Host

Abstract: The genome of the food-borne pathogen Campylobacter jejuni contains multiple highly mutable sites, or contingency loci. It has been suggested that standing variation at these loci is a mechanism for rapid adaptation to a novel environment, but this phenomenon has not been shown experimentally. In previous work we showed that the virulence of C. jejuni NCTC11168 increased after serial passage through a C57BL/6 IL-10-/- mouse model of campylobacteriosis. Here we sought to determine the genetic basis of this adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 64 publications
(92 reference statements)
8
117
2
Order By: Relevance
“…The work by Jerome et al (2011) supports the proposed model. These researchers demonstrated that passage of C. jejuni NCTC11168 through C57Bl6 IL10-deficient mice increased colonization and disease symptoms, and this process was accompanied by phase variation in specific contingency genes.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The work by Jerome et al (2011) supports the proposed model. These researchers demonstrated that passage of C. jejuni NCTC11168 through C57Bl6 IL10-deficient mice increased colonization and disease symptoms, and this process was accompanied by phase variation in specific contingency genes.…”
Section: Discussionsupporting
confidence: 67%
“…Illumina sequence analysis of these bacterial populations demonstrated that the genetic changes observed during animal passage occurred almost exclusively in contingency genes, strongly suggesting that phase variation in contingency genes during passage in chickens and/or mice in our study is directly responsible for enhanced colonization and disease. Jerome et al (2011) did not, however, directly link changes in any one contingency gene to increased colonization and disease.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…While an allele may be mildly deleterious or confer no fitness advantage over other forms under one set of environmental conditions [6], that allele may become beneficial if the environment changes. As selection can act only on available variation, SGV provides a potential means for more rapid adaptive evolution ( [7][8][9][10][11][12][13][14][15][16][17][18][19][20]; reviewed in [21]) compared with the de novo mutations [5,22], particularly if the environment changes (e.g. if a new predator or competitor invades the system, or if abiotic conditions change).…”
Section: Introductionmentioning
confidence: 99%